Bacterial Infections in Acute-on-Chronic Liver Failure - Yang, Lingling; Wu, Tianzhou; Li, Jiang; Li, Jun (Seminars in Liver Disease, 2018)
Acute-on-chronic liver failure (ACLF) is a newly recognized clinical syndrome characterized by preexisting chronic liver disease or cirrhosis with organ failure and high 28-day mortality (50–90%). Bacterial infections (BIs) play pivotal roles in the development and progression of ACLF either as a main precipitating event or a specific complication. The main organisms isolated as triggering ACLF are Gram-positive bacteria, followed by Gram-negative bacteria. Spontaneous bacterial peritonitis, pneumonia, urinary tract infections, and skin infections are prevalent infections that trigger and complicate ACLF. Despite appropriate antibiotic treatment, BIs account for poor ACLF outcomes and lead to a worse clinical course and higher intensive care unit admission and short-term mortality. Early diagnosis and novel nonantibiotic methods are highly important for managing BIs. Thus, this review focuses on the epidemiology, prognosis, and diagnosis of and management strategies for BIs in ACLF patients as well as the relationship between BIs and ACLF.
Keywords: bacterial infections; acute-on-chronic liver failure; prognosis; prophylaxis